In utero combined di-(2-ethylhexyl) phthalate and diethyl phthalate exposure cumulatively impairs rat fetal Leydig cell development. (15th February 2018) - Hu, Guoxin; Li, Junwei; Shan, Yuanyuan; Li, Xiaoheng; Zhu, Qiqi; Li, Huitao; Wang, Yiyan; Chen, Xiaofang; Lian, Qingquan; Ge, Ren-Shan
Highlights: Phthalates dose-dependently cause fetal Leydig cell aggregation. DEHP is more potent to inhibit testosterone production than DEP. DEP and DEHP can elicit dose addition effect on FLC development. Abstract: Phthalate diesters, including di-(2-ethylhexyl) phthalate (DEHP) and diethyl phthalate (DEP), are chemicals to which humans are ubiquitously exposed. Humans are exposed simultaneously to multiple environmental chemicals, including DEHP and DEP. There is little information available about how each chemical may interact to each other if they were exposed at same time. The present study investigated effects of the combinational exposure of rats to DEP and DEHP on fetal Leydig cell development. The results showed that the gestational (GD12-20) exposure of DEP + DEHP resulted in synergistic and/or dose-additive effects on the development of fetal Leydig cell. The lowest observed adverse-effect levels (LOAEL) for fetal Leydig cell (aggregation and cell size), and StAR expressions were of 10 mg/kg and, lower than when these chemicals were exposed alone. Also, mathematical modeling the response curves supports the dose-addition model over integrated-addition model. Overall, these data demonstrate that individual phthalate with a similar mechanism of action can elicit cumulative, dose additive, and sometimes synergistic, effects on the development of male reproductive system when administered as a mixture.